Two Belgian Local Breeds and One Commercial Strain - Moula, N.; Antoine-Moussiaux, N.; Farnir, F.; Leroy, P. (International Journal of Poultry Science, 2009)
In the context of the global threat on the genetic diversity loss in poultry breeding, there is an urgent need to broaden our knowledge about local breeds. In particular, economically exploitable traits can be sought in these breeds in an attempt to motivate and to concentrate the needed conservation programs. The present study aims at evaluating egg quality in two Belgian local breeds (the Ardennaise and the Famennoise) and to compare it with a commonly bred commercial strain (Lohmann brown). Two criteria are used here to describe egg quality: egg composition (measured through yolk to albumen ratio) and its stability during conservation (measured through pH). Egg weight, size, composition as well as albumen pH were measured on 140 eggs. Measures were performed at days 0, 7, 14 and 21 after laying. The egg weight was highest in the Lohman strain (62.86 g), intermediate in the Famennoise breed (55.51g ) and lowest in the Ardennaise (50.31g). On the opposite, yolk to albumen ratio was significantly higher in the Ardennaise (0.53) compared to the Famennoise breed (0.49) and the Lohmann strain (0.43). Albumen pH at laying was lowest in the Lohmann compared to the local breeds. However, no statistical difference between the three breeds could be detected for this parameter at day 14 or 21 post-laying. While high pH in local breeds eggs is often reported to be caused by a lesser conservation ability, the present results discard such a conclusion, rather suggesting some physiologically higher pH at laying not resulting from defaults in conservation. As a measure of egg freshness, pH norms must thus be adapted to the various poultry breeds.